The Influence of Horizontal Reinforcement on Punching Shear Strength - Ameen, Ali N.; Al-Sherrawi, Mohannad H. (Engineering, Technology & Applied Science Research, 2024)
The slab is more petite and space-efficient in flat plate buildings since it is supported directly by columns rather than beams or drop panels, allowing additional floors to be added. Despite these benefits, a flat plate slab is vulnerable to brittle punching shear, a catastrophic collapse caused by the abrupt propulsion of a slab piece out from underneath by a column. In this study, Finite Element Analysis (FEA) was provided and carried out in ABAQUS/CAE 2019 to model the effects of punching shear impact on a flat plate reinforced with horizontal steel bars that vary in position, diameter, and number. Concrete was represented in the model by 8-noded hexahedral 3D brick elements and steel reinforcements by 2-noded linear 2D beam elements. The model has been modified according to the results of the experiments. In order to determine how different quantities and sizes of horizontal steel bars placed at different locations in a flat plate affected the slab's performance, parametric analysis was conducted. According to the outcomes, the shear capacity increases between 0.37 and 9.85% as the diameter of bars increases, between 1.2 and 22.9% as the quantity of bars increases, and between 1.99 and 26.1% as the bars shift from the tension side to the compression side.